2016
DOI: 10.1186/s12915-016-0281-2
|View full text |Cite|
|
Sign up to set email alerts
|

Type IV collagen drives alveolar epithelial–endothelial association and the morphogenetic movements of septation

Abstract: BackgroundType IV collagen is the main component of the basement membrane that gives strength to the blood–gas barrier (BGB). In mammals, the formation of a mature BGB occurs primarily after birth during alveologenesis and requires the formation of septa from the walls of the saccule. In contrast, in avians, the formation of the BGB occurs rapidly and prior to hatching. Mutation in basement membrane components results in an abnormal alveolar phenotype; however, the specific role of type IV collagen in regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 75 publications
(49 reference statements)
1
29
0
Order By: Relevance
“…Type IV collagens localize to the basement membrane of epithelial and interstitial endothelial cells where SCMFs are anchored. In previous reports, postnatal inactivation of Type IV collagen caused defective ELN production and deposition, and defects in alveologenesis and epithelial cell differentiation (Loscertales et al, 2016). In our study, we also found significant changes in multiple integrins (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Type IV collagens localize to the basement membrane of epithelial and interstitial endothelial cells where SCMFs are anchored. In previous reports, postnatal inactivation of Type IV collagen caused defective ELN production and deposition, and defects in alveologenesis and epithelial cell differentiation (Loscertales et al, 2016). In our study, we also found significant changes in multiple integrins (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…A complementary set of mammalian genetic, genomic, physiologic, and three-dimensional morphologic approaches have pointed to myofibroblasts and extracellular matrix constituents, such as elastin, as key players in these latestage CDH-associated pulmonary abnormalities. 27,50 Lipofibroblasts, a lipid-containing population of interstitial fibroblasts first identified during the canalicular phase of lung development, were also reduced in rats treated with the CDH-inducing teratogen nitrofen. 51,52 Lipofibroblast signaling is critical for the completion of alveologenesis, possibly in directing the production of surfactant phospholipids in type 2 pneumocytes.…”
Section: Pulmonary Hypoplasia and Alveolarization Defects In Cdhmentioning
confidence: 99%
“…Reduced elastic fiber deposition may be responsible for the abnormal alveolar walls in patients with CDH, 102 more specifically, defects of secondary alveologenesis possibly linked to insufficient fibroblast growth factor-18 expression. 103 Reduced tropoelastin and elastin fibers result in stunted secondary septa with immature alveolar myofibroblasts ectopically displaced into the lung interstitium, 50,103 where they disrupt oxygen exchange. 27 Because this phenotype mimics the pathologic findings in humans surviving with CDH, it offers a good model in which to test for therapeutic rescue.…”
Section: Studies Of Alveolar Septation In Cdh Modelsmentioning
confidence: 99%
“…For example, reducing mechanical tension from fetal breathing by depleting the amniotic fluid or lowering the stiffness of cell culture surface favors AT2 over AT1 cell differentiation (6). Loss of an extracellular matrix protein, COL4A1, also leads to an increased ratio of AT2 to AT1 cells (7). Inside the epithelial cells, betacatenin-mediated canonical WNT signaling as well as fibroblast growth factor signaling inhibit AT1 cell differentiation (6,(8)(9)(10) and HDAC3-dependent TGF-beta signaling is required for proper epithelium expansion and AT1 cell spacing (8,11).…”
mentioning
confidence: 99%